CLASSROOM LEARNING ENVIRONMENTS WITH MOBILE ASSISTED LANGUAGE LEARNING - Justin P. Pool; Haruyo Yoshida (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
This presentation intends to show how common mobile assisted language learning (MALL) applications that focus on receptive skills can be complemented with a curriculum that emphasizes more productive skills. The research to be presented measured two groups of adult learners’ language growth after they were subjected to a commonly used MALL application focusing on reading, listening, grammar, and vocabulary, and a 15-week classroom course involving instruction on communication, presentation skills, and training learners to mitigate their tendencies to fear and avoid errors. Learners were measured via standardized testing, instructor observation, and learner reflection. Both groups experienced a significant increase in their TOEIC scores; however, learners in the Group 2 failed to increase their TOEIC reading scores. Both the instructor and students reported an increase in communicative confidence and competence. Learners also improved their presentation skills. The difference between the two groups most likely lies in the fact that 14 out of 15 members of group one completed 100% of the online segment of the course, while only 10 out of 16 members of the second group completed even 50% of the online segment. The presentation will also highlight the value of using MALL applications focusing on receptive skills despite the fact that they may score lowly in evaluation models due to their lack of interactivity.